LIBRARY RESOURCES AND SERVICES AND PUBLICATION PRODUCTIVITY - A.N., Zainab (Malaysian Journal of Library and Information Science, 2001)
Present the results of a study that compares the perceived adequacy of library resources for research, the formal channels found to be useful in providing information needed for research, the methods used to keep abreast with current research literature, the problems faced when obtaining information required for research with publication productivity of 83 academic engineers and 239 academic scientists from the University of Malaya and National University of Malaysia. Respondents’ views were sought on how libraries can improve their services to support research activities. The feedback from interviewing 56 academic scientists and engineers about the results obtained from the survey is also presented. The services that correlate positively are inter-library loans and help from library staff in searching online databases. The sources, which correlate with high total publication scores are research reports, conference proceedings and library accession lists. Scientists who used varied methods to keep themselves up-to-date with current research literature are highly productive. The highly productive scientists indicated the following situations as problematic for them when searching information needed for research: no help in finding information, not knowing where to look for information, not finding relevant information, receiving information too late, and not knowing how to choose relevant databases. This indicates that the productive scientists do need help in obtaining information. The respondents also gave useful suggestions on how library services could be improved to support research effectively.